Innovative Teaching Strategies for Information Technology and Engineering Students - Kahare, Muhini L.; Howe, Emmanuel L. (Journal of Research in Education and Pedagogy, 2025)
In our technologically globalized world, higher education teachers need to adjust themselves to modern teaching techniques to help students learn easily and be innovative. Integration of Information, Communication, and Technology (ICT) assists teachers in meeting the demand for technology-based teaching and learning tools. Innovative teaching tools are facilities that are currently replacing traditional teaching methods. In the fields of computer science and engineering, information and communication technology (ICT) innovative teaching approaches are regarded as one of the most crucial components for advanced teaching and learning. Teaching in Higher education is facilitated by a variety of software programs, apps, and information management systems. Innovative teaching encourages students’ engagement and cultivates the spirit of creativity. For engineering students to succeed in their fields of study, they need to have intrinsic motivation toward learning. Educators who are teaching computer science and engineering courses are required to be creative and use innovative teaching approaches to engage every student. The purpose of this paper is to share strategic knowledge with fellow lecturers in the field of computer sciences and engineering on how to effectively teach and engage students using various tools that are available on the internet and at our disposal. The focus of this paper was on innovative teaching strategies that students prefer to use in their studies. Findings from the study highlighted that most of the students preferred practical teaching methods and industry projects. Evidence was gathered from students enrolled under the Faculty of Engineering and Technology from Eswatini, Botswana, and Namibia campuses using a purposive sampling.